Jawabanmu

2014-07-15T20:10:09+07:00
P - 2s = 1 -----> p = 2s + 1
q - r = -1 ------> r = q + 1
2r - q = -1 -----> q = 2r + 1
s - 2p = 1 -----> s = 2p + 1

-------------------------------------------------------------------------------------

(s = 2p + 1) disubtitusikan pada (p = 2s + 1)
p = 2s + 1
p = 2(2p + 1) + 1
p = 4p + 2 + 1
p - 4p = 3
-3p = 3
p = -1 . subtitusikan pada (s = 2p + 1) sehingga

s = 2p + 1
s = -2 + 1
s = -1

-----------------------------------------------------------------------------------------------

(r = q + 1) disubtitusikan pada (q = 2r + 1)

q = 2r + 1
q = 2(q + 1) + 1
q = 2q + 2 + 1
q - 2q = 3
-q = 3
q = -3 . subtitusikan pada (r = q + 1) sehingga

r = q + 1
r = -3 + 1
r = -2

jadi p + q + r + s = (-1) + (-1) + (-3) + (-2) = -7






1 5 1